SYLLABİC METER İN AZERBAİJANİ POETRY: LİNGUİSTİC CRİTERİA AND PHONETİC POTENTİAL - Malakhat Vidadi Gizi Ahmadova (Research Focus International Scientific Journal, 2025)
This article analyzes the syllabic meter, widely used in the tradition of Azerbaijani poetry, from linguistic and phonetic perspectives. The system, based on the stability of syllable count, is structured in accordance with the phonetic features of Turkic languages, particularly the Azerbaijani language. The study is grounded in Mammad Aliyev’s theoretical views on syllabic meter and examines poetic elements such as phonetic structure, rhythmic pauses (caesuras), rhyme, and other stylistic devices. A comparative approach is also used to highlight the distinctive characteristics of Azerbaijani poetry in relation to other Turkic literary traditions. The research sheds light on the linguistic foundations of the syllabic meter and emphasizes its significance in both literary heritage and contemporary poetic processes.